No Hepatitis Delta Virus Seropositivity among Blood Donors with Overt and Occult Hepatitis B Infection in Dalian, Liaoning Province, China - Deng, Xuelian; Liu, Dan; Delcourt, Maelenn Pailine; Gao, Huihui; Zhou, Lu; Candotti, Daniel (Viruses, 2023)
Hepatitis delta virus (HDV) is an obligate satellite of hepatitis B virus (HBV). Dual HDV/HBV infection is associated with down-regulated HBV replication and fast progression to severe liver disease. Although HDV is transmissible through exposure to infected blood, data about HDV infection in blood donors remain scarce. Between 2011 and 2021, 869,633 donations were collected from prequalified donors in Dalian, China. In total, 1060 (0.12%) were confirmed HBsAg and/or HBV DNA-reactive. Subsequently, anti-HDV IgG was tested in 2175 donations, including 65 that tested HBsAg+ pre donation, 1017 confirmed HBV-positive (507 HBsAg+/HBV DNA+, 33 HBsAg+/DNA−, 477 HBsAg-/DNA+ (451 occult (OBI) and 26 acute infections)), 327 viral DNA non-repeated-reactive, 397 anti-HBc-only, and 369 anti-HBs-only. Two (0.09%) samples tested anti-HDV IgG weakly reactive but were unconfirmed by IgM and IgG repeat testing with alternative assays, suggesting an initial false reactivity. In addition, HDV testing in a subgroup of confirmed OBI donors, comprising 451 donors from Dalian and 126 archived samples of OBI donors from around the world, showed only one non-Chinese donor to be repeatedly anti-HDV-reactive, suggesting that HDV/HBV coinfection does not play a significant role in the genesis of OBI. The overall data suggested an extremely low prevalence of HDV infection among blood donors in Liaoning province, Northeast China.